Synthetic Routes Towards the Synthesis of Geminal α‐Difunctionalized Ketones. Issue 10 (3rd February 2021) - Day, David P.; Vargas, Jorge A. M.; Burtoloso, Antonio C. B.
Abstract: The importance of gem ‐difunctionalized ketones is represented by their broad applications across chemical boundaries over recent years. The interesting reactivities that this class of compounds possess have made them ideal building blocks to access high‐value organic molecules. Furthermore, the gem ‐difunctionalized ketone moiety has featured in numerous bioactive molecules. For these reasons, a plethora of routes to access such significant molecules have been developed by research groups worldwide – this account looks at delineating the synthesis of gem ‐difunctionalized ketones from carbonyl substrates, diazo compounds, sulfur ylides and alkynyl reactants. Abstract : The synthetic routes towards the synthesis of geminal α‐difunctionalized ketones is presented in this account. The coverage includes numerous synthetic routes from carbonyl, diazo, sulfur ylides and alkynyl derived substrates.